Remarks on Doryphoribius flavus (Iharos, 1966), and description of three new species (Tardigrada, Hypsibiidae) - Lisi, Oscar (Zootaxa, 2011)
The author examined paratypes of Doryphoribius flavus (Iharos, 1966) (formerly Hypsibius (Isohypsibius) flavus Iharos, 1966), and the holotype and paratypes of D. citrinus (Maucci, 1972) (which is considered a junior synonym of D. flavus), furnishing new details, both qualitative and metric, to the description of the species, and providing a discussion on the synonymy. Specimens, previously attributed to these species, from Amazonia, South Africa, and Bali, were also examined and proved to belong to three species new to science: Doryphoribius amazzonicus sp. nov., Doryphoribius bindae sp. nov., and Doryphoribius solidunguis sp. nov. Doryphoribius amazzonicus sp. nov. has a reticular cuticular ornamentation with ridges forming a tubercle at each crossing; legs lacking cuticular ornamentation; buccal tube slightly longer than in D. flavus with respect to the body length, stylet supports inserted on the buccal tube in a slightly more caudal position; peribuccal papulae present; teeth and ridges appear to be absent in the buccal cavity; pharyngeal bulb with apophyses and two macroplacoids; claws slightly shorter and stouter than in D. flavus. Accessory points and smooth lunules present. No other cuticular thickening present on the legs. Doryphoribius bindae sp. nov. has a delicate reticular cuticular ornamentation formed by narrow ridges with a tiny tubercle at each crossing; a fine reticular design present on the legs; peribuccal papulae present, buccal armature with only one dorsal tooth near the medial margin of each stylet sheath. Pharyngeal bulb with apophyses and two macroplacoids. Accessory points and small lunules present. No other cuticular thickening present on the legs. Doryphoribius solidunguis sp. nov. has a very obvious reticular cuticular ornamentation with an irregular shape and size mesh (usually large) delimited by thick, sometimes protruding ridges that may form tubercles at crossings; cuticle of the legs smooth; peribuccal papulae present and two pairs of dorsal teeth lying along the anterior margins of the stylets sheaths. Pharyngeal bulb with apophyses and two macroplacoids. The claws are large and stout with very small accessory points; lunules present, those of the inner claws more evident than in similar species; a cuticular bar is present on the first three pairs of legs. Doryphoribius flavus was considered widespread, but this work exposing cryptic species indicates that the geographic distribution is more restricted.